SALPINGECTOMY AT THE TIME OF CESAREAN DELIVERY: A SYSTEMATIC REVIEW - Ratu Alicia, Dea Nabila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Candidates for tubal sterilisation include women who have finished having children and who are looking for a method of birth control that is both highly effective and permanent. It is possible for it to be carried out at any point during a woman's menstrual cycle, as well as right after a child is born or an abortion is performed. Hysteroscopy, laparoscopy, or even a mini-laparotomy might be performed instead. It is important to have a conversation about the danger of regret as well as the characteristics that increase the likelihood of regret, such as a young age at the time of sterilization (less than 30 years), a lower parity, sterilization administered in the immediate postpartum period, divorce or remarriage following sterilization, and being poor or of Hispanic origin. It would appear that being a young adult at the time of the sterilization is the most significant indicator of regret. It is extremely important to keep in mind that this does not provide full protection. According to the findings of the CREST study, the failure rate across all procedures was 18.5 out of every 1000 procedures over the course of a 10-year period. Even in the event that a cesarean birth is performed unexpectedly, a mother request for postpartum permanent contraception in the form of bilateral total salpingectomy during cesarean delivery may be a procedure that is both safe and practicable.